Perjanjian dalam Perkawinan Perspektif Hukum Islam dan Perundang-Undangan - Ru’fah Abdullah (Jurnal Studi Gender dan Anak, 2017)
Getting married is an act which is praised by The Prophet Muhammad, because it was recommended to Allah’s messengers and prophets firstly before advised towards people, in order to present the meaning that getting married is very important for human being, and it must be paid attention and applied by Muslims. In applying this recommendation all couple expect to get happy life in this world and the hereafter. Some people believe that this strong expectation can be gotten truly within completing all material facilities, besides having heartfelt, creed and confidence. But, in the conditions some couples do not have more stronger when the problems of life in household come and take turns; in fact one of them with his powerful dominates to each other, and then gets rid of the other’s rights. Thus, the article presents about making agreement in married life as a solution for the problems of household and keeping the rights of everyone. The methods of presenting here are using all references in Islamic traditions, combined to the legislations and regulation of Indonesian constitution. It gives the new horizon of study in this case.